Publicness in Education Through Alienation and Shared Experiences of Negativities - Rüsselbaek Hansen, Dion (Philosophical Inquiry in Education, 2026)
In this response paper, I begin by carefully engaging with the concerns raised during the symposium “Reclaiming the Publicness of Education” at the Nordic Education Research Association (NERA) conference held in Helsinki, Finland, in March 2025. I do so by highlighting key issues addressed by each of the contributing authors in relation to these concerns. Drawing inspiration from psychoanalytical theory (Lacan, 1997; McGowan, 2024) and political philosophy (Sloterdijk, 2016), I then reflect on how publicness—as a vital realm in education—can be conceptualized and embraced as central to what makes education educational. In this regard, I draw on notions of alienation, emancipation, and displacement. Importantly, I do not approach publicness as a shared realm in a positive, socio-symbolic sense within education. Rather, I argue for a conception of publicness as a space where subjects—understood as whatever-beings (singular subjects) without fixed determinations and beyond identities—can share their negativities (experiences of non-belonging, lack, and absence) in common. This, I contend, opens up possibilities for restructuring—and even a disruption—of the unequal socio-symbolic order that is typically foreclosed. This foreclosure, I posit, stems from, for example, the fixation of this order around dominant symbolic positions and identities, which tend to contaminate public realms with private interests in education.